Tinjauan Teologis Mengenai Konsep Purgatory dan Implikasinya Terhadap Soteriologi [Theological Review of the Concept of Purgatory and Its Implications for Soteriology] - Suparman Suparman; Bimo Setyo Utomo; Dahlia Juliadil Veronica Zebua (Universitas Pelita Harapan, 2024)
The concept of purgatory or what is known as purification is one of the concepts that the Catholic Church believes as a truth for those who during their lifetime had a close relationship with God, but were still not pure enough to enter heaven, so a purification process is needed. The Catholic Church provides the basis of Bible verses and Deuterocanonics to support its teachings and the process will take place according to the sins that have been committed while living in this world. This research uses qualitative methods with a library approach. Using the literature method, the researcher will explain the concept of purgatory in the teachings of the Catholic Church from accurate sources, originating from Catholic circles themselves which will be reviewed theologically-critically to find that the concept of purgatory is contrary to the redemptive work of Jesus Christ on the cross. In the end, the concept of purgatory is not in accordance with what God has stated in His Word and has implications for soteriology, namely: Jesus is the only way of salvation, salvation is a grace, and praying for the dead is not Biblical.BAHASA INDONESIA ABSTRACT: Konsep api penyucian atau yang dikenal dengan istilah purifikasi merupakan salah satu konsep yang diyakini Gereja Katolik sebagai sebuah kebenaran bagi mereka yang semasa hidupnya memiliki hubungan yang dekat dengan Tuhan, namun masih belum cukup murni untuk masuk surga, sehingga diperlukan proses pemurnian. Gereja Katolik memberikan dasar ayat-ayat Alkitab dan Deuterokanonika untuk mendukung ajarannya dan prosesnya akan berlangsung sesuai dengan dosa yang telah dilakukan selama hidup di dunia. Penelitian ini menggunakan metode kualitatif dengan pendekatan kepustakaan. Dengan menggunakan metode kepustakaan, peneliti akan menjelaskan konsep api penyucian dalam ajaran Gereja Katolik dari sumber-sumber yang akurat, yang berasal dari kalangan Katolik sendiri yang kemudian akan ditinjau secara teologis-kritis untuk menemukan bahwa konsep api penyucian bertentangan dengan karya penebusan Yesus Kristus di kayu salib. Pada akhirnya, konsep api penyucian tidak sesuai dengan apa yang telah Tuhan nyatakan dalam Firman-Nya dan berimplikasi pada soteriologi, yaitu: Yesus adalah satu-satunya jalan keselamatan, keselamatan adalah anugerah, dan mendoakan orang mati tidak Alkitabiah.